Value Chain Analysis on Goat Processed Products in Surabaya - Berto Mulia Wibawa; Dewie Saktia Ardiantono; Ywang Nara Pragnya (School of Business, IPB University (SB-IPB), 2019)
One livestock commodity that has the potential to supply the people's need for the protein is goat, but the distribution of goat meat in Surabaya and its processed products can be said to be limited if compared to the superior commodities such as chicken and beef. This phenomenon may be caused by limited knowledge of value-added products, distribution of goat and goat processed products. The objective of this research was to establish a value chain recommendations of goat commodity. The qualitative method was used in this research and the data were collected from business actors in goat commodity through semi-structured face-to-face interviews and analyzed by value chain method analysis. The findings of this research show that there are 17 products that can increase goat commodity added value. Managerial implications are generally addressed to business players of Micro, Small, Medium Entreprises (MSMEs) and prospective business actors of processed goat products to be able to maximize the potential of goat livestock, which is aimed to improve product quality and added value of the product itself.Keywords: goat, value chain analysis, processed food, MSME, commodity